MODERATING EFFECT OF MANAGERIAL AND PROFSSIONAL ASSISTANCE ON INNOVATION STRATEGY AND ACADEMIC SPIN-OFF MANAGEMENT - Oscar Chrismadian Noventa (Universitas Airlangga, 2021)
The university is required to commercialize the results of research and knowledge of the university through academic spin-off. Academic spin-off benefit for stimulating the economy, creating job growth and innovation. However, academic spin-off find difficulty in offering products and services to the market because of the lack of knowledge related to managerial and resource management. Means commonly used to overcome this obstacle is to establish a business incubator in the form of a centralized facility that provides access, support and university policy. Business Incubator helps new academic spin-off stand to better understand the market and to provide guidance in the initial phase of the establishment of academic spin-off. This study aimed to examine the moderating effect of the assistance provided university business incubator in the election strategy of innovation and academic spin-off performance. The study was conducted at 76 academic spin-off in Yogyakarta and Semarang. In this study developed a theoretical model by proposing three hypotheses to be tested using regression analysis. The survey results revealed that academic spin-off conduct exploitation strategy proved a positive influence on the performance of academic spin-off. Instead, academic spin-off conduct proven exploration strategy negatively affect academicspin-off performance. Furthermore, managerial and professional assistance as moderating variables are proven to be able to strengthen the relationship between innovation strategy and academic spin-off performance. Keywords: Academic Spin-off , Managerial and Professional Assistance, Academic Spin-offPerformance